Enhancing nano indentation properties of Al 7075 alloy: The role of silver addition - Mariyam Sattar; Raja M Umer; Muhammad Punhal Sahto; Mamoon Aamir; Mohammed A. Tashkandi; Lioua Kolsi (Results in Engineering)
Al 7075, valued for wide applicability in aerospace structures, remains prone to environmental degradation in harsh environments. Alloying can improve its hardness and elastic modulus. Unlike traditional reinforcements, silver (Ag) offers inherent hardness and resilience against environmental conditions. Additionally, it refines the microstructures to reduce pits and stress corrosion cracking. Therefore, this research employs experimental and numerical procedures to investigate the effects of Ag addition on the nanoindentation properties of Al 7075. The hardness and elastic modulus of Al 7075 with 1 %, 2 %, 3 %, and 4 % Ag by weight are measured through nanoindentation tests using a Berkovich indenter. Results show that 1 %, 2 %, and 4 % Ag additions enhanced hardness and elastic modulus, with the maximum values recorded for 4 % Ag. The 3 % Ag sample, though, had an unexpected reduction in hardness and modulus attributed to Statistically Stored Dislocations (SSDs) and Geometrically Necessary Dislocations (GNDs). Analysis of indenter depth and pile-up through the scanning probe microscope (SPM) and X-ray Diffraction (XRD) revealed that the specimen with 1 % and 4 % Ag by weight exhibit the highest and lowest values of deformation respectively. The experimental results are validated numerically and a good conformity is observed. Results indicate that Ag addition improves the mechanical properties of Al 7075, and makes it is a potential material for aerospace and high-stress applications.